2021
DOI: 10.1007/s00442-021-04906-x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly low paternal diversity is associated with infrequent pollinator visitation for a bird-pollinated plant

Abstract: Unexpectedly low paternal diversity is associated with infrequent pollinator visitation for a bird-pollinated plant 1Oecologia Highlighted Student Paper: We examined the mating system of a bird-pollinated herb to test the prediction that bird pollination leads to high paternal diversity. Contrary to expectations, we found very low paternal diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…Paternity diversity was approximately half of the produced seed number in this species. This value was relatively high compared with that of other plant species, such as Bombax ceiba (3.7 paternity for 31.3 seeds/plant) and Anigozanthos humilis (3.5 paternity for 9.2 seeds/plant), but it was less than that of Arabidopsis halleri (22.4 paternity for 26.7 seeds/plant; Llaurens et al, 2008; Kestel et al, 2021; Xiang et al, 2022). Depositions of pollen grains by multiple insects or by insects that have a large pollen carryover may result in higher paternity diversity (Karron et al, 2006; Mitchell et al, 2013).…”
Section: Discussionmentioning
confidence: 83%
“…Paternity diversity was approximately half of the produced seed number in this species. This value was relatively high compared with that of other plant species, such as Bombax ceiba (3.7 paternity for 31.3 seeds/plant) and Anigozanthos humilis (3.5 paternity for 9.2 seeds/plant), but it was less than that of Arabidopsis halleri (22.4 paternity for 26.7 seeds/plant; Llaurens et al, 2008; Kestel et al, 2021; Xiang et al, 2022). Depositions of pollen grains by multiple insects or by insects that have a large pollen carryover may result in higher paternity diversity (Karron et al, 2006; Mitchell et al, 2013).…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, the congeneric L. orbifolia showed consistently low levels of outcrossing across natural (t m = 0.72) and restored (t m = 0.57) populations and high levels of correlated paternity across natural (r p = 0.15) and restored (r p = 0.18) populations (Coates & Hamley, 1999;Monks et al, 2021). Here, rarity and naturally small population size may provide an explanation for these results (Coates et al, 2007) equivalent, and are among the lowest recorded for plants globally (Kestel et al, 2021;Krauss et al, 2017). An r p of 0.07 equates to an estimate of the effective number of sires (1/r p ) of 14.3, an exceptionally high value for a relatively small plant, and reflects the combination of (i) a long flowering season; (ii) few receptive flowers per plant at any one time; (iii) moderate-to-low plant density within populations; and (iv) effective pollination by highly mobile bird pollinators exhibiting behaviour that leads to diverse pollen loads, pollen carryover and extensive movement of pollen.…”
Section: Popmentioning
confidence: 74%
“…Bird pollination can lead to more effective pollen transfer between different individual plants and thus more outcrossing, which can also occur over larger distances (Table 5, Ford et al 1979;Beardsell et al 1993b;Frick et al 2014;Krauss et al 2017;Kestel et al 2021). They have larger home ranges and visit more flowers because they require more nectar to support their metabolism than much smaller, cold-blooded insects (Sampson et al 1989;Frick et al 2014;Bezemer et al 2016).…”
Section: Genetic Consequences Of Pollination Syndromesmentioning
confidence: 99%
“…Paternal diversity is relatively high in bird pollinated plants in the Proteaceae and Myrtaceae (Byrne et al 2007;Frick et al 2014;Bezemer et al 2016). However, low paternal diversity was associated with bird pollination in Anigozanthos humilis, which is primarily pollinated by western spinebills and brown honeyeaters (van der Kroft et al 2019;Kestel et al 2021). Studies designed to guide seed collection found that wind-pollinated plants had a high degree of genetic continuity over broad (4 sp.)…”
Section: Genetic Consequences Of Pollination Syndromesmentioning
confidence: 99%
See 1 more Smart Citation